2023
DOI: 10.3389/fpsyg.2023.1122264
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning the future for families running away from war: Challenges and resources of Ukrainian parents in Italy

Abstract: Since February 2022, 7.8 million people have left Ukraine. In total, 80% are women and children. The present quali-quantitative study is the first in Italy to (i) describe the adaptation challenges and the resources of refugee parents and, indirectly, of their children and (ii) investigate the impact of neuropsychopedagogical training on their wellbeing. The sample includes N = 15 Ukrainian parents (80% mothers, mean age = 34 years) who arrived in Italy in March and April 2022. The parents participated in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
(86 reference statements)
0
4
1
Order By: Relevance
“…Berezka (2022) adds a psychological aspect to this, as the psychology of communication is the key to successful adaptation to the educational space. At the same time, the study revealed a significant number of children with adaptation disorders, in particular, the emotional spectrum disorder in displaced children, which contradicts the obtained data (Paoletti et al, 2023;Rousseau & Guzder, 2008). It can be the result of directly experienced traumatic events related to war or the loss of loved ones.…”
Section: Discussioncontrasting
confidence: 69%
“…Berezka (2022) adds a psychological aspect to this, as the psychology of communication is the key to successful adaptation to the educational space. At the same time, the study revealed a significant number of children with adaptation disorders, in particular, the emotional spectrum disorder in displaced children, which contradicts the obtained data (Paoletti et al, 2023;Rousseau & Guzder, 2008). It can be the result of directly experienced traumatic events related to war or the loss of loved ones.…”
Section: Discussioncontrasting
confidence: 69%
“…Resilience: relevance to refugees. Resilience is a crucial element of mental and emotional well-being for refugees affected by the ongoing conflict between Russia and Ukraine, as they face various stressors and adversities (Vus & Esterlis, 2022;Paoletti et al, 2023). Social support, coping mechanisms, and positive emotions are key to fostering resilience (Walsh, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence rates, as well as risk factors associated with mental health in those populations, vary widely among studies 3,6,[34][35][36] . Most recent evidence shows that sleep disturbances, mental health problems, and speci c fears are frequently reported in Ukrainian refugees and IDPs 36, 37 .…”
Section: Discussionmentioning
confidence: 99%